2007
DOI: 10.1039/b703445h
|View full text |Cite
|
Sign up to set email alerts
|

Structure and nuclearity of active sites in Fe-zeolites: comparison with iron sites in enzymes and homogeneous catalysts

Abstract: Fe-ZSM-5 and Fe-silicalite zeolites efficiently catalyse several oxidation reactions which find close analogues in the oxidation reactions catalyzed by homogeneous and enzymatic compounds. The iron centres are highly dispersed in the crystalline matrix and on highly diluted samples, mononuclear and dinuclear structures are expected to become predominant. The crystalline and robust character of the MFI framework has allowed to hypothesize that the catalytic sites are located in well defined crystallographic pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
216
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(226 citation statements)
references
References 194 publications
(274 reference statements)
6
216
2
2
Order By: Relevance
“…9,10 In general, such catalysts also have Brønsted acidity, either since the standard procedures for Cu or Fe exchange do not result in a complete exchange or new protonic sites are formed as a result of a reduction of the metal ions. 11 It is argued that the exchanged Cu or Fe ions facilitate the SCR reaction 9,12-14 by oxidizing the NO to NO 2 , while the SCR reaction takes place elsewhere in the zeolite, 15,16 which could be on the ammonia adsorbed on the Brønsted sites. If the Brønsted sites are located close to the Cu (or Fe) ions in the zeolite, it is conceivable that an NO 2 molecule on a Cu ion can interact directly with an NH 3 molecule on a neighboring Brønsted site, which would make a reaction possible without the need for desorption of NO 2 .…”
Section: Mechanistic Aspects Of the Scr Reactionmentioning
confidence: 99%
“…9,10 In general, such catalysts also have Brønsted acidity, either since the standard procedures for Cu or Fe exchange do not result in a complete exchange or new protonic sites are formed as a result of a reduction of the metal ions. 11 It is argued that the exchanged Cu or Fe ions facilitate the SCR reaction 9,12-14 by oxidizing the NO to NO 2 , while the SCR reaction takes place elsewhere in the zeolite, 15,16 which could be on the ammonia adsorbed on the Brønsted sites. If the Brønsted sites are located close to the Cu (or Fe) ions in the zeolite, it is conceivable that an NO 2 molecule on a Cu ion can interact directly with an NH 3 molecule on a neighboring Brønsted site, which would make a reaction possible without the need for desorption of NO 2 .…”
Section: Mechanistic Aspects Of the Scr Reactionmentioning
confidence: 99%
“…A lot of studies have been recently devoted to Fe-ZSM-5, which is considered as a model catalyst that helps understands catalytic reactions by these materials. 8 Fe-ZSM-5 was shown to be very efficient not only in the N 2 O decomposition but also in the oxidation of alkenes and aromatics using N 2 O as oxidant. 9,10 According to several authors, it has been concluded that the common feature of these two reactions catalyzed by Fe-ZSM-5 is the formation of adsorbed oxygen atoms called "R-oxygen" or "O ads " (eq 1).…”
Section: Introductionmentioning
confidence: 99%
“…Based on kinetics, spectroscopic and modeling studies, mono-and binuclear iron-oxo species have been proposed as the potential active sites rather than clustered oxide species. 5,6 Modeling approaches play a crucial role due to the unusually low content of active iron species (around 3 Â 10 18 sites g À1 ) 7 preventing univocal spectroscopic experimental assignments. Indeed a detailed knowledge of a mechanism occurring between reactants and solids can be reached by combining energetic and kinetic of elementary steps with a macroscopic description of the reaction.…”
Section: Introductionmentioning
confidence: 99%